180 Patient care in units for rapid diagnosis and orientation in internal medicine. (23rd September 2015) - Konate, A; Rullier, P; Bonnin, M; Robles, G; Lequellec, A
Abstract : Context and Objectives: In the Montpellier University Hospital Center, 30% of emergencies refer to the Internal Medicine Pole. Age, polypathology, congestion of the downstream network lead to an increased average length of stay in the Pole, with difficulties to find adequate beds for unscheduled patients. Patients endure increasing waiting times in Emergencies and waiting lists for scheduled stays, inadequacies in care, and undue lengths of hospitalisation. To address this problem, the Hospital decided to create a new Unit for Diagnosis and Fast Referring in Internal Medicine (DIAGORA). The project DIAGORA aims to: better regulate the admission of patients from Emergencies to Internal Medicine, improve consistency of care by ensuring within 72 h patient's comprehensive evaluation and referral to an appropriate downstream unit or return at home, reduce patient's average length of stay by anticipating the organisation of discharge from the time of admission in DIAGORA; therefore, contribute to increase the Internal Medicine Pole supply for scheduled care on specific activities such as oncology, immunopathology, addictions, vascular disease, psychosomatic. Programme: Started in November 2008, the project DIAGORA enrolled in a process of Assessment of Professional Practice (EPP), aiming to model, accompany and assess the organisation and partnership required. The project involved the medical and paramedical teams and Social and Administrative services. The methodological, technical and evaluative support was implemented by the EPP team of the Hospital. The approach mainly relied on methods of process analysis and monitoring of indicators. Before the implementation of DIAGORA, a process analysis led with the professionals allowed to define the admission criteria, the target clinical path and the priority action plan to be set up. The medical, paramedical and administrative organisation was formalised through a Chart. Rules of partnership were collectively defined by the involved teams, and included in the Chart. Finally, indicators and assessment modalities were defined and their production organised in partnership with the Decision-making computing team of the Hospital. Since the opening of DIAGORA in April 2009, the EPP Team supported the monitoring of actions and the analysis of indicators and partnership. Automation of dashboards from the hospital information system and collection of indicators by DIAGORA allowed the revaluation on 1st, 3rd, and 6th months. A follow-up of the partnership was realised through planned meetings with the partners, using the results of the revalued indicators. Results: The assessment of DIAGORA after 6 months shows consistent results even above the expected targets. The capacity of admission of unscheduled care in Internal Medicine has increased by 20%. Patients are admissible in DIAGORA within 1 h (40% immediately). The average length of stay of patients in Internal Medicine units has decreased by 1.5 days (exceeding the target). The irrelevant prioritisation in requests for imaging has decreased from 23% to 10%. Patient's referral to a downstream unit is effective within 72 h on average. Moreover, on the 1st month 40% of the patients returned home after discharge from DIAGORA (the target was 20 % after 6 months). And the recruitment of the Internal Medicine Pole on the scheduled specific care to develop has increased by 15%. Discussion: All partners express a positive opinion on DIAGORA. The partnership with Gerontology will be extended in 2010. Progress remains to achieve, especially about transport times from Emergencies to DIAGORA, which can double the delay of admission. Other issues are the delay in obtaining Holter results and the transmission of information to the Internal Medicine units. DIAGORA carries on the revaluation of its indicators, with the aim to achieve complete automation. Conclusion: Collegiality in defining organisation and partnership, Chart formalisation, seniorization of patient's admission, evaluation and referral, anticipation of patient's discharge, monitoring and regular reporting of indicators, all these factors have allowed to build trust between partners around the care of patients, and to obtain results often exceeding the targets. The evaluation of DIAGORA after 6 months confirms the interest of the Assessment of Professional Practice approach to improve the response to patient needs and the quality of health. Contexte-objectifs: Au CHRU de Montpellier, 30% des Urgences sont orientées vers le Pôle Cliniques Médicales. L'âge, la polypathologie, l'engorgement des filières d'aval entraînent un allongement des DMS du Pôle, d'où difficultés croissantes à trouver un lit adapté pour les patients non programmés et allongement des listes d'attente pour les séjours programmés. En découlent des délais d'attente accrus aux Urgences, des prises en charge inadéquates, des durées d'hospitalisation indues. En réponse à ce problème, l'établissement a créé en 2009 une Unité de Diagnostic et d'Orientation Rapide de Médecine Interne (DIAGORA) pour accueillir, évaluer et orienter les patients provenant des Urgences. Le projet DIAGORA a pour objectifs de: mieux réguler l'admission en filière de Médecine Interne à partir des Urgences, améliorer la cohérence de prise en charge en assurant en 72 h l'évaluation complète du patient et l'orientation d'aval adéquate, réduire la DMS en Médecine Interne de ces patients en anticipant l'organisation de la sortie dès l'admission à DIAGORA, afin d'augmenter l'offre de soins programmés du Pôle Cliniques Médicales sur des activités spécifiques (oncologie, immunopathologie, addictions, vasculaire, psychosomatique). Programme: Dès son lancement en novembre 2008, le projet DIAGORA s'est inscrit dans une démarche d'Evaluation des Pratiques Professionnelles (EPP), visant à modéliser, accompagner et évaluer l'organisation et le partenariat nécessaires. Les équipes médicales et paramédicales (Urgences, Cliniques Médicales, Imagerie, Gérontologie), le Service Social et les gestionnaires ont été impliqués d'emblée. L'Equipe EPP du CHRU a réalisé l'accompagnement méthodologique, technique et évaluatif. La démarche a utilisé les méthodes d'analyse de processus et de suivi d'indicateurs. Préalablement à la mise en place de DIAGORA, une analyse de processus menée avec les professionnels a permis de définir les critères d'admission, le parcours patient cible et le plan d'actions prioritaires. Une Charte d'Organisation médicale et paramédicale a été formalisée sur cette base. Des règles de partenariat validées par les équipes concernées ont été intégrées à la Charte. Enfin, les indicateurs ont été définis et leur évaluation organisée en partenariat avec l'Informatique Décisionnelle du CHRU. Après l'ouverture de DIAGORA en avril 2009, l'Equipe EPP a poursuivi l'accompagnement des actions et l'analyse des indicateurs d'activité et de partenariat. L'automatisation de tableaux de bord à partir du SIH et le recueil d'indicateurs par DIAGORA ont permis la réévaluation à 1, 3 et 6 mois. Un suivi du partenariat a été réalisé lors de réunions régulières avec les partenaires. Resultats: L'évaluation de DIAGORA à 6 mois montre des résultats conformes voire supérieurs aux objectifs : la capacité d'accueil des séjours non programmés de Médecine Interne a augmenté de 20%. Le délai d'admissibilité du patient à DIAGORA est inférieur à 1 h (immédiat pour 40%). En aval, la DMS des patients en hospitalisation a diminué de 1, 5 jours (objectif à 6 mois dépassé). Les priorisations non pertinentes d'examens d'imagerie sont passées de 23% à 10%. L'orientation vers l'aval est effective sous 72 h en moyenne. Dès le premier mois 40% des patients retournent au domicile en sortie de DIAGORA (l'objectif était de 20% à 6 mois). Enfin, le recrutement des Cliniques Médicales sur les activités programmées spécifiques a augmenté de 15%. Discussion: Le retour des partenaires lors des réunions de suivi est positif. Le partenariat avec la Gérontologie sera renforcé en 2010. Des progrès restent à réaliser, en particulier sur les temps de transport des Urgences à DIAGORA, le délai d'obtention des résultats de Holter et la transmission des informations aux unités d'aval. DIAGORA poursuit la réévaluation régulière de ses indicateurs, dans l'optique d'une automatisation complète. Conclusion: La définition collégiale et la formalisation en Charte, la seniorisation de l'admission et de l'orientation d'aval, l'anticipation de la sortie, le suivi et la communication périodique des indicateurs, ont permis d'établir la confiance entre partenaires autour de la prise en charge des patients et d'obtenir des résultats dépassant les objectifs initiaux. Le bilan de DIAGORA à six mois confirme l'intérêt d'une démarche d'EPP pour améliorer la réponse aux besoins des patients et la qualité de l'offre de soins.